UBE2J2 is essential for the progression of meiosis prophase I during spermatogenesis in mice - Xiaochen Yu; Jie Cen; Yaxuan Zhang; Tongtong Li; Mingyu Zhang; Fei Gao; Hongbin Liu; Yongzhi Cao (iScience, 2025)
Summary: The coordination of numerous proteins is necessary for spermatogenesis, including degradation through the ubiquitin-proteasome pathway. Ubiquitin binding enzyme E2 (UBE2J2) is involved in the degradation of endoplasmic reticulum-associated proteins, while its role in spermatogenesis remains unclear. We found that Ube2j2−/− mice exhibit azoospermia and spermatocytes undergo meiotic arrest at the mid-pachytene stage. Examining homologous recombination (HR) markers indicated that HR intermediate complexes are unstable and fail to form crossovers in Ube2j2−/− spermatocytes. Proteomics analysis uncovered an extensive suite of meiosis- and chromosome segregation–associated proteins unexpressed in mouse spermatocytes lacking functional UBE2J2. Our findings suggest that UBE2J2 could possibly play a key role in SC disassembly, ensuring meiosis can proceed in the late pachynema during male germline cell development in mice, and serves as an essential factor in meiotic recombination and spermatogenesis.